PERENCANAAN PUSAT BUDAYA ADAT PASER DENGAN PENDEKATAN TIPOLOGI ARSITEKTUR DI KABUPATEN PASER - Silalahi, Natalia Debora; Baharuddin, Faizal; Huda, Khoirul (LPPM Universitas 17 Agustus 1945 Samarinda, 2021)
The Paser Indigenous Cultural Center is a place that provides knowledge and an overview of the many paser cultures. The problem of the cultural center is that research on traditional architectural paser is still lacking, so the initial step is to determine typology into the concept of traditional architectural paser. The purpose of this study is to plan the Paser indigenous Cultural Center with the concept of traditional Paser architecture trought theÂ approach of architectural typology according to Raphael Moneo, namely the form of space, building functions and image/ faÃ§ade (focus). With the aim of portraying a typical Paser building faÃ§ade by identifying 3 traditional Paser building, namely the jami mosque, sadurengas museum and the traditional house of Kutakunalenja based on the roof, walls, doors, windows, colors and carvings as â€œVocal Pointsâ€ on the concept of building form. The research methods are data collection, analysis, concept and drawing. From the results of the discussion of the analysis of the relationship of space with an area of 23,796 mÂ² of Building Base Coefficient, 35,396 mÂ² of Green Base Coefficient of 10 maases with the main mass in the building.Â Keyword : Cultural Center, Typology, Paser